ANALISIS MINAT KUNJUNGAN KEMBALI KE KLINIK KECANTIKAN DI KOTA BATAM - Jessica Jessica; Dame Afrina Sihombing (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Abstract: As a tourist destination, Batam offers a variety of interesting destinations to discover, from the center of rotation, to culinary tourism, marine tourism, and now beauty tourism that is developing in the city. Indonesia has also presented its tourism industry since the Covid-19 pandemic. Beauty can be used to improve the economy of a community using tourism that carries the concept of economic-based tourism. A study conducted in Batam aims to identify the factors that influence the interest in returning to a beauty clinic. A resident of Batam city visited a beauty clinic. It is a quantitative research conducted by distributing questionnaires to respondents. For the study, 403 respondents completed the questionnaire. Purposive sampling was used in this study, and IBM SPSS Statistics 20 was used for testing. The study found that destination image, perceived quality, perceived value, atmosphere, and service quality variables have a significant impact on the dependence variable for revisit intention.Keywords : Destination Image, Perceived Quality, Perceived Value, Service Quality, Intention to revisit